The Role of Forensic Laboratory Results in Proving Document Forgery Criminal Offenses: Peran Hasil Laboratorium Forensik dalam Pembuktian Tindak Pidana Pemalsuan Dokumen - Dona Febiani; Benny Sumardiana (Annual Review of Legal Studies, 2024)
Implementation of proof in court should rightfully involve judges evaluating all evidence submitted to the court, including the results of forensic laboratory examinations. However, in reality, in some cases, judges overlook the results of forensic laboratory examinations in proving the crime of document forgery. Therefore, this research aims to understand and analyze the role of forensic laboratory examination results in supporting the proof of document forgery, as well as the considerations of judges in placing and evaluating forensic laboratory examination results used as evidence in court. This study employs a juridical-empirical research method with a qualitative approach using primary and secondary data sources. Data validity is ensured using triangulation techniques, while data analysis is conducted through qualitative narrative analysis. The research findings indicate that: 1) Forensic laboratory examination results on documents play a crucial role in supporting the proof of document forgery crimes, as they can be used by investigators to ascertain the authenticity of a document, aid in identifying suspects, and serve as evidence tools such as expert testimony and/or exhibits in court to support prosecution. 2) Judges assess the validity of forensic laboratory examination results by examining the methodology used in the examination and the credibility of forensic experts in conducting the analysis. Furthermore, forensic laboratory examination results can assist judges in deliberating alongside other relevant and supportive evidence. Therefore, judges may render verdicts with at least two valid pieces of evidence accompanied by their conviction. In conclusion, the findings affirm that forensic laboratory examination results can serve as valid evidence in court, playing a crucial role in supporting the proof of document forgery crimes. These results can influence judges in decision-making and aid in uncovering document forgery crimes.